Strength of concrete masonry units with plastic bottle cores - Wonderlich, Sean M. (Kansas State University, 2014)
Concrete masonry units are a common method of construction in the world. Since the masonry units can be constructed with ease. Fifty billion water bottles are consumed every year. Lack of waste management and recycling in third world countries has come to the attention of many organizations. The use of plastic bottles in construction materials has been around for the past twenty years, but with little focus on using full plastic bottles in the materials. The Engineers Without Borders student group on the campus at Kansas State University have found a way to utilize the full 500-mL plastic bottle in the creation of concrete walls. The bottles laid horizontally with concrete on both sides and as mortar between the bottles was used. These bottles create large voids in the wall decreasing the compressive strength of the wall. This thesis presents the results of a study conducted to determine the compressive strength of concrete masonry units with plastic bottle cores. The plastic bottles were used to create the center voids in the masonry units. Concrete was placed around the bottles to encase them in the masonry units. The study utilized 500-mL plastic bottles from five different water companies placed inside masonry units of 7.87-inch wide by 8.26-inch high by 15.75-inch long (200-mm wide by 210-mm high by 400-mm long) in size and analyzed the resultant compressive strength. The testing for compressive strength was determined according to the ASTM C140 standard. Results from this study were deemed reasonable due to the testing of concrete cylinders as a control compressive strength. Determination of the compressive strength of the concrete masonry units allows for further study to continue in concrete masonry units with plastic bottle cores to determine if they are viable in third world countries.
Keywords: Plastic bottle; Civil engineering; Concrete; Masonry unit; Construction; Third world; Civil Engineering (0543)